Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1007/bf01715137
|View full text |Cite
|
Sign up to set email alerts
|

In patients with BCR-ABL-positive ALL in CR peripheral blood contains less residual disease than bone marrow: Implications for autologous BMT

Abstract: Residual leukemic cells are detectable at frequencies as low as 1 in 10(6) normal cells in patients with Philadelphia chromosome/BCR-ABL-positive leukemias in complete remission (CR) using reverse-transcriptase polymerase chain reaction (RT-PCR) with specific nested primers. The level of minimal residual disease (MRD) in the bone marrow (BM) and the peripheral blood (PB) may favor one of the two as the source for an autologous graft. In order to quantify MRD with RT-PCR we analyzed patients ficolled cells afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
1
18
1
Order By: Relevance
“…29 Similarly, Martin et al have found that Bcr-Abl levels were about 35-fold lower in PB than in BM of 6 patients with Ph ϩ ALL. 30 However, others observed similar levels in PB and in BM. 31,32 Potential causes of the difference in MRD levels and kinetics between PB and BM that are associated with imatinib include redistribution of the blasts and different susceptibility to this agent (eg, due to distinct proliferative properties of leukemic blast cells in these compartments).…”
Section: Discussionmentioning
confidence: 88%
“…29 Similarly, Martin et al have found that Bcr-Abl levels were about 35-fold lower in PB than in BM of 6 patients with Ph ϩ ALL. 30 However, others observed similar levels in PB and in BM. 31,32 Potential causes of the difference in MRD levels and kinetics between PB and BM that are associated with imatinib include redistribution of the blasts and different susceptibility to this agent (eg, due to distinct proliferative properties of leukemic blast cells in these compartments).…”
Section: Discussionmentioning
confidence: 88%
“…We previously found median 1.5 log lower RT-PCR titers in unmobilized peripheral blood as compared to bone marrow in nine paired samples from remission patients 26 and hypothesized that PBSC grafts might be superior to BM grafts due to a significantly lower level of residual leukemia. In another small series of four G-CSF-mobilized leukapheresis samples there was a trend for even lower RT-PCR titers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proven that the levels of MRD in peripheral blood and bone marrow correlate well in T-ALL, but that the correlation is weak in B-cell precursor ALL, with a generally lower peripheral blood MRD. [9][10][11][12][13] Surprisingly, only a few reports have explored the prognostic impact of MRD in peripheral blood, although sampling peripheral blood is far more comfortable for patients and easier for clinicians than aspirating bone marrow. Brisco et al…”
Section: Introductionmentioning
confidence: 99%